PRARANCANGAN PABRIK BIODIESEL BERBAHAN BAKU TANAMAN NON-PANGAN BIJI KEMIRI SUNAN DENGAN KAPASITAS 100.000 TON/TAHUN - , DANU PURWANUGRAHA, Ahmad Tawfiequrrahman Y., S.T., M.T., D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary design of biodiesel plant whom uses Kemiri Sunan and Methanol as main raw materials is intended to asses the feasibility of this plant. Biodiesel plant is designed to fulfill 100.000 ton/year of capacity and to be operated continuously 330 days/year. In order to gain the biodiesel product as designed capacity, 9832.75 ton/year of methanol 99,85% (w/w) and 263.762,09 ton/year of Kemiri Sunan seed are required as main raw materials. The synthesis of biodiesel is two step reactions, first step is esterification and second step is transesterification. The reaction takes place in Continuous Stirred Tank Reactor (CSTR) at atmospheric pressure and temperature of 600C. Decanter is used to purify biodiesel and distillation column is used to recover methanol. To be constructed in Karawang, West Java, this plant requires 2 ha area and employs 216 labors. The consumed energy includes electricity of 887,86 kWh/year and 9583,2 m3/year of fuel oil. Moreover, the utility requires 186561,22 kg/hour of make-up water. Fixed capital costs 45,488,577.29 + Rp. 103.566.745.309,53 and working capital costs $ 11,433,284.97 + Rp. 174.442.823.340,67. Based on the economical feasibility study, this plant is classified as low risk chemical plant with 32,90% of ROI (before taxes)